STRATEGI PEMBELAJARAN BERBASIS MULTIPLE INTELLIGENCES - Endang Kusniati (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2016)
This  paper   discusses  strategies based  learning   multiple   intelligences.  Which   has   focused  on the  concept of multiple  intelligences based learning  strategies, training  and  developing 8 (eight)  value  of intelligence (Multiple Intelligences) and  the  contribution of multiple  intelligences learning  strategy  based on National Education. Theory of multiple intelligences triggered  by Howard  Gardner,  is used  as an analytical tool, ie linguistic, logical-mathematical, spatial, musical, kinesthetic, interpersonal, and intrapersonalnya, natural.  To know  the  trend  of the  intelligence of every child in the  concept of multiple  intelligences will be tested using the research of Multiple Intelligences Research (MIR). With MIR teachers will be easier  knowing  the tendency of students’  intelligence. While the contribution of MI in the national  education is to terbinanya based schools multiple intelligences, such as SDIT-SMPIT Al-Bina Pangkalpinang, SMP YIMI Gresik, and 95 other schools